Probabilistic Safety Analysis and Risk-Based Inspection of nuclear research reactors: state-of-the-art and implementation proposal (Brazilian Journal of Radiation Sciences, 2021)
Industrial facilities systems deteriorate over time, thus increasing the possibility of accidents. Risk-Based Inspection (RBI) classifies such systems by their risk information with the purpose of prioritizing inspection efforts. RBI can reduce inspection activities, resulting in lower risk levels, and maintaining reliability and safety in acceptable levels. Risk-Informed In-Service Inspection (RI-ISI) is a RBI approach used in nuclear industry. RI-ISI uses outcomes from Probabilistic Safety Analysis (PSA) of Nuclear Power Plants (NPP) to plan In-Service Inspections (ISI). Despite nuclear research reactors are simpler and have lower risks than power reactors, the application of PSA to them may be useful for safety improvements once they are more flexible, provide easier access to its core and allow changes in fuel configurations. Ageing management of components is also required to assure continued adequacy of safety levels, reliable operation, and compliance with operational limits and conditions. This includes periodic review of ISI programs in which monitoring of material deterioration is considered, and that can be supported by the RBI approach. A review of state-of-the-art of PSA and RBI and an implementation proposal applied to nuclear research reactors is presented in this work, as well as its application to a TRIGA reactor using computer codes developed by ReliaSoft® Corporation.